E-learning readiness during the school suspension caused by the COVID-19 pandemic: A case of English language teachers in Sabah, Malaysia - Hu Ke; Asmaa AlSaqqaf (Pejabat Karang Mengarang UPSI, 2022)
The quick spread of COVID-19 across the world has badly affected all aspects of human life, especially the educational sector. In Malaysia, all the educational institutions were closed to comply with the lockdown promulgated by the Malaysian government in response to the COVID-19 pandemic in the country. Yet, the teaching and learning process had to be continued during this period, and that was carried out through a full resort to e-learning. This study investigates the level of readiness among secondary school English language teachers to utilize e-learning in teaching during the lockdown in Kota Kinabalu, Sabah. Psychological readiness, technological skills readiness, and content readiness, adopted from Chapnick's (2000) readiness model, were the main dimensions to investigate. A total of 83 online cross-sectional surveys were received and analyzed using descriptive analysis. The construct validity of the measuring items was performed by the exploratory factor analysis, and the instrument reliability was obtained at an acceptable level. Results showed that although the secondary school English language teachers in Kota Kinabalu were technologically ready to use e-learning in teaching, they had unsatisfactory readiness levels for psychological, content, human resource, and equipment readiness. Importantly, the current research stresses the need to develop an up-to-date survey that technically and comprehensively addresses the various aspects of the advanced technological skills that should be mastered by teachers and educators in this era of the Fourth Industrial Revolution (IR4.0). Limitations of the study and recommendations for future research are also highlighted.